Hippocratic Screening of Pineapple Peel (Ananas comosus (L.) Merr) Water Extracts - Alamanda, Baiq Irzana Putri; Mardiyah, Raudatul; Aini, Siti Rahmatul (Jurnal Biologi Tropis, 2024)
Pineapple (Ananas comosus (L.) Merr.) is the fruit with the highest production in Indonesia, with West Nusa Tenggara as one of the largest producers. However, high pineapple production causes an increase in pineapple peel waste. Pineapple peel has potential as a traditional medicine because it contains beneficial compounds. This study aims to conduct a hypocratic screening on pineapple peel water extract to determine its pharmacological activity. The research method involved the use of Swiss Webster mice as test animals, where pineapple peel water extract was administered intraperitoneally in five doses (1, 10, 100, 300 and 1000 mg/KgBW). Observations were made on the mice's physical activity every 5 minutes for 4 hours, and continued after 2, 4, and 7 days of treatment. The results showed significant stimulant activity in the central nervous system (CNS) at certain doses, characterized by changes in the physiological activity of mice. Symptoms include increased motor activity, hyperemia, and diarrhea.